Application of Kinematic Wave Model for Simulation of Advance - Recession Trajectories under Furrow Irrigation - R. Ravi Babu; T.B.S. Rajput; Purnima Mishra (Journal of Soil and Water Conservation, 2022)
Field experiments were conducted on the sandy loam soil of research farm of Water Technology Centre, IARI to study the hydraulics of flow under furrow irrigation. Kinematic wave furrow irrigation model was calibrated and validated for simulation of water front advance-recession trajectories. The model simulation showed good agreement with field observations. Further, the sensitivity analysis revealed that model predictions are highly sensitive to infiltration function parameters, furrow geometry and inflow rate.